Analisis Kesalahan Siswa dalam Pemecahan Masalah Penjumlahan dan Pengurangan Berdasarkan Teori Polya pada Kelas 1 Sekolah Dasar - Synta Nur Khasanah; Ryky Mandar Sary; Veryliana Purnamasari (Departement of Mathematics Education, 2024)
This study aims to analyze the types of student errors and the factors causing these errors in solving addition and subtraction problems based on Polya's theory. The research employs a qualitative approach with a phenomenological method, involving 10 students and the first-grade teacher from an elementary school as subjects. Data collection techniques include student interviews, teacher interviews, written tests, and documentation. Data analysis techniques involve data collection, data reduction, data presentation, and verification. The results indicate that the types of student errors based on Polya's theory are: 1) misunderstanding the problem with a percentage of 14%, 2) planning errors with a percentage of 7%, 3) executing the plan errors with a percentage of 7%, and 4) reviewing errors with a percentage of 60%. The factors causing these errors include: 1) students not being accustomed to writing down what is known and what is asked, 2) not understanding the steps to be used, 3) lack of accuracy in calculations and rushing, and 4) not knowing the concept of conclusions and a lack of carefulness in solving problems.